Pengaruh Kualitas Produk, Inovasi Produk, Dan Gratis Ongkir Terhadap Keputusan Pembelian Produk Macaronicuk Studi Kasus Reseller Macaronicuk Provinsi Jawa Timur - Papank Abi Sadewa; Budi Wahono; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyse the effect of product quality variables, product innovation and free shipping on purchasing decisions for Macaronicuk products. This research uses a case study on Macaronicuk resellers in East Java Province. Determination of the number of samples using the saturated sample formula and obtained results as many as 35 respondents in accordance with the total population. Data collection was carried out using a questionnaire. To solve the problems in this study using SPSS assistance with data analysis methods used in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, t test, coefficient of determination (R²) test. The results showed that the product quality variable had an effect on purchasing decisions, while product innovation and free shipping had no effect on purchasing decisions. Keywords: Product Quality, Product Innovation, Free Shipping, Purchasing Decisions.